2018
DOI: 10.7897/2230-8407.09573
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Denaturation by Extracts of Leaves, Stems and Roots of Pisonia Grandis R.BR.

Abstract: Pisonia grandis R.Br. is a rural folkloric medicinal plant of Nyctaginaceae family and has been extensively used as an anti-diabetic and antiinflammatory agent.The present study is aimed to evaluate the in-vitro anti-arthritic activity of the solvent extracts and the column fractionates of this plant. Denaturation of tissue protein is a proven cause of inflammatory and arthritic diseases. Inhibition of protein denaturation is a measure of anti arthritic activity. The petroleum-ether and ethanol extract concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…31 . In-vitro assessment of anti-arthritic potential of pet-ether and ethanol extract of leaves, stems and root was carried out by Poongothai et al 32 The study revealed that the petether and ethanol extracts of leaves exhibited significant anti-arthiritic potential equivalent to that of palmitic acid at the same concentration. In yet another assay of a biherbal extract composed of ethanolic extract of Pisonia grandis and cardiospermum helicacabum, indicated a greater inhibition of protein denaturation compared to the individual extracts 33 .…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…31 . In-vitro assessment of anti-arthritic potential of pet-ether and ethanol extract of leaves, stems and root was carried out by Poongothai et al 32 The study revealed that the petether and ethanol extracts of leaves exhibited significant anti-arthiritic potential equivalent to that of palmitic acid at the same concentration. In yet another assay of a biherbal extract composed of ethanolic extract of Pisonia grandis and cardiospermum helicacabum, indicated a greater inhibition of protein denaturation compared to the individual extracts 33 .…”
Section: Antidiabetic Activitymentioning
confidence: 99%